The role of key regions in spatial development - Raphael Niklas Becker; Marcel Henkel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
We discuss the role of key regions in spatial development. Local productivity shocks can affect the entire economy as they expand via tight connections in the domestic production network and in uence the geographical allocation of labor. In particular, we identify the set of key regions with the highest potential to affect aggregate productivity, output, and welfare. Key regions are central locations with strong spatial linkages in the production network but are not too large and congested so they can still attract additional labor in response to positive productivity shocks without local rents and input costs rising too much. Using a spatial equilibrium model and data from German districts, we find that a relatively modest development of productivity in key regions lowered German output and welfare growth by a factor of two from 2010 to 2015.
Keywords: R10; R12; R15; F10; F1; F16; O4; O51; 330; Regional trade; Input-output linkages; Labour mobility; Spatial economics; Economicgeography; Regional productivity; Sectoral productivity